A novel multifactorial hamstring screening protocol: association with hamstring muscle injuries in professional football (soccer) – a prospective cohort study - Lahti, Johan; Mendiguchia, Jurdan; Edouard, Pascal; Morin, Jean-Benoit (Biology of Sport, 2022)
The aim of this pilot study was to analyze the potential association of a novel multifactorial hamstring screening protocol with the occurrence of hamstring muscle injuries (HMI) in professional football. 161 professional male football players participated in this study (age: 24.6 ± 5.36 years; body-height: 180 ± 7.07 cm; body-mass: 77.2 ± 7.70 kg). During the pre- and mid-season, players performed a screening protocol consisting of 11 tests aimed to evaluate their performance in regards to four main musculoskeletal categories: posterior chain strength, sprint mechanical output, lumbopelvic control and range of motion. Univariable cox regression analysis showed no significant association between the isolated test results and new HMI occurrence during the season (n = 17) (p > 0.05). When including injuries that took place between the pre- and mid-season screenings (~90 days), maximal theoretical horizontal force (F0) was significantly associated with higher HMI risk between pre- and mid-season evaluations (n = 14, hazard ratio; 4.02 (CI95% 1.08 to 15.0, p = 0.04). This study identified that 1) no single screening test was sufficient to identify players at risk of HMI within the entire season, while 2) low F0 was associated with increased risk of HMI when occurring closer to the moment of screening. The present results support the potential relevance of additionally including frequent F0 testing for HMI risk reduction management. Replication studies are needed in larger cohorts for more accurate interpretations on “univariable and multivariable levels levels. Finally, future studies should explore whether improving F0 is relevant within a multifactorial HMI risk reduction approach.